Understanding Differential Development of Imbalance as Predictive of Risk for Behavioral Outcomes Among Justice-Involved Youth - Wojciechowski, Thomas (Journal of developmental and life-course criminology, 2023)
This study sought to understand developmental heterogeneity in dual systems model imbalance. Furthermore, the study sought to examine relevance of imbalanced development for understanding behavioral outcomes. The Pathways to Desistance data were used in analyses. Group-based trajectory modeling was used to estimate heterogeneity in dual systems imbalance development. Mixed effects modeling was used to estimate the effects of imbalance on outcomes of interest. Findings indicated that a three-group developmental model of imbalance best fit the data. Assignment to the group characterized by consistently high sensation-seeking and consistently low impulse control was associated with increased risk for reporting engagement in all outcomes of interest (general offending, violent offending, heavy episodic drinking, marijuana use). Imbalance in dual systems development characterized by high levels of sensation-seeking and low impulse control predicts an increased risk for deviant behavioral outcomes. Problematic imbalanced development should be identified so as to mitigate the risk for behavioral issues during adolescence and emerging adulthood.